2018
DOI: 10.1073/pnas.1720032115
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus internalization is regulated by a size-dependent endocytic pathway

Abstract: SignificanceFlaviviruses are a globally important group of human viral pathogens. These viruses enter cells by hijacking an endocytic pathway, clathrin-mediated endocytosis, used by cells to take up growth factors and nutrients. While most cargo is small, virions are large, and we identified host factors specifically required for the internalization of large cargo including these viruses. These studies define a set of requirements for viral internalization and which may be amenable to therapeutic interventions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 36 publications
3
89
0
2
Order By: Relevance
“…We validated that YFVΔSK/Nluc gene expression was neutralized by YFV-specific antibodies and was dependent on several known pathways of flavivirus entry, including clathrin-and dynamin-mediated endocytosis (10,30,(65)(66)(67), endosomal acidification (45,(66)(67)(68)(69), E protein-dependent fusion (31), and dependence on LY6E (32,33) and RPLP1 (34).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We validated that YFVΔSK/Nluc gene expression was neutralized by YFV-specific antibodies and was dependent on several known pathways of flavivirus entry, including clathrin-and dynamin-mediated endocytosis (10,30,(65)(66)(67), endosomal acidification (45,(66)(67)(68)(69), E protein-dependent fusion (31), and dependence on LY6E (32,33) and RPLP1 (34).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, YFV-mediated Nluc expression was reduced by genetic ablation of LY6E ( Fig. 2H), a host factor that facilitates internalization of flaviviruses and other viruses (32,33), or by RNAi-mediated knockdown of RPLP1 ( Fig. 2I), a ribosomal protein required for efficient flavivirus translation (34).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Once attached to cells, flaviviruses are taken up by clathrindependent endocytic vesicles. While this same host machinery is involved in the internalization of multiple types of cellular cargo, recent studies identified host molecules required by flaviviruses to exploit the endocytic pathway for infectious entry including RNASEK, lymphocyte antigen locus 6 (LY6E) and microtubules [43][44][45] . Flavivirus membrane fusion occurs in the low pH compartments of the endosome and is catalysed by conformational changes in the E protein that involve the formation of E protein trimers, penetration of the highly conserved E-DII fusion loop into the adjacent host membranes and the folding of the E protein helical stem against the exterior surface of the newly formed E protein trimer 46 .…”
Section: E-diismentioning
confidence: 99%
“…The initial events of ZIKV entry have been identified [10][11][12]; but data regarding its fate thereafter are limited. Upon attachment to a permissive cell, ZIKV crosses the plasma membrane via clathrin-and mucolipin-2-dependent endocytosis, accompanied by formation of LY6E tubules [13,14]. The dependence of ZIKV on endocytosis has been confirmed in a variety of cell models [15].…”
mentioning
confidence: 89%